ECG ANOMALY DETECTION USING AUTOENCODERS (International Journal of Food and Nutritional Sciences, 2022)
While the big data revolution takes place, large amounts of electronic health records, such as electrocardiograms (ECGs) and vital signs data, have become available. These signals are often recorded as a time series of observations and are now easier to obtain. In particular, with the rise of smart devices that can perform ECG, there is the quest for developing novel approaches that allow monitoring these signals efficiently, and quickly detect anomalies. However, since most data generated remains unlabeled, the task of anomaly detection is still very challenging. Unsupervised representation learning using deep generative models has been used to learn expressive feature representations of sequences that can make downstream tasks, such as anomaly detection, easier to execute and more accurate. We propose an approach for unsupervised representation learning of ECG sequences using an autoencoder and use the learned representations for anomaly detection using multiple detection strategies. We tested our approach on the ECG5000 electrocardiogram dataset of the UCR time series classification archive. Our results show that the proposed approach is able to learn expressive representations of ECG sequences, and to detect anomalies with scores that outperform other both supervised and unsupervised methods.